Fórum de Escolas pela Paz do Grande Bom Jardim: enfrentamentos às dinâmicas da violência armada em periferias de Fortaleza - Cavalcante, Laisa Forte (2021)
The state of Ceará has one of the most worrisome youth homicide scenarios in the country. These rates and the territorial disputes of factions in the peripheries affect some important social facilities, such as public schools. Even during the COVID-19 pandemic in Ceará, homicide numbers continued on an upward curve. In this context, this dissertation has as a general objective to map actions engendered from the articulation of public schools in the region of Grande Bom Jardim (GBJ) aimed at confronting the effects of armed violence in the daily lives of students, teachers and administrators. In this sense, our specific objectives are: to discuss strategies produced by public schools in the GBJ to confront the effects of gun violence in their daily lives and to problematize group devices with young people from these school territorialities for collective analysis and production of shared care in the face of these effects. Methodologically, this is an intervention-research, in the light of the ethos of cartography, articulated with extension actions of VIESES-UFC in GBJ. The methodological strategies involve monitoring and participating in the actions of the Forum of Schools for Peace in GBJ and the construction of group devices, through thematic workshops with students from a high school in GBJ, as a result of our participation in the Forum's actions. The analysis of the research corpus was done by means of cartographic analysis, using the Field Journal as an implicit narrative. The results produced are the strategies of resistance that we participated in and composed together with the School Forum: monthly meetings with managers, teachers and partners; artistic-cultural mobilizations that give visibility to the lives of youth and produce memory of young people murdered by the dynamics of armed violence that pervades their daily lives; formative moments and rounds of conversations with education professionals about collective care in mental health; joint development of documents and production of knowledge; art and culture festival, a space for sharing experiences and visualization of culture and art of young people from GBJ and the III Festival of Youth, an event that proposed to enhance debates on various topics, besides building connections and valuing arts developed by student-artists. Furthermore, we produced group devices, from the extension action "Bom de Papo", with young people from a school territory for collective analysis and production of shared care in the face of the effects of armed violence, such as: fear and hopelessness, limits of movement due to territorial factionalization, loss of friends and family and institutional violence in their daily lives, seeking to strengthen the protective role of school and the permanence of young people in this equipment. Finally, it is hoped that this research can contribute to studies in Psychology, Education and other areas that focus on processes of subjectivation, resistancepractices, collective mobilizations, art and culture developed and embodied in peripheral territories.